Consumer Insights on Halal Certification: Awareness, Perception, and Visibility as Key Determinants of Purchase Behaviour - Mohamad Isa Abd Jalil; Siti Hajar Samsu; Debrina Puspita Andriani; Shariff Umar Shariff Abd. Kadir; Habib Ahmed (Bank Indonesia, 2026)
This study investigates consumer insights on halal certification in Malaysia by examining awareness, perception, visibility, trust, and purchase behaviour, with religious belief as a moderator. Using a non-probability purposive sampling method, 801 valid responses were collected and analysed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perception and awareness significantly influence trust, while visibility has no significant effect. Trust and religious belief strongly predict purchase behaviour, and religious belief also moderates the relationship between trust and purchase. It should be noted, however, that the sample disproportionately represents Indigenous Sabah respondents, while Malay respondents—the national majority—are underrepresented. Therefore, the findings are context-specific and not generalisable to the entire Malaysian population. Despite this limitation, the study provides useful insights into consumer trust in halal certification and offers practical recommendations for practitioners, regulators, and policymakers, as well as theoretical contributions for future research. Acknowledgment This paper was supported by the Geran Penyelidikan Dana Kluster (DKP) Fasa 1/2023 (DKP0020). The authors gratefully acknowledge the financial support provided through this grant, which has facilitated the implementation of this research. The authors also sincerely thank the journal’s editors and reviewers for their valuable comments and suggestions that helped improve the quality of this paper.